2010
DOI: 10.1007/s00167-010-1322-y
|View full text |Cite
|
Sign up to set email alerts
|

Tendon-grasping strength of various suture configurations for rotator cuff repair

Abstract: Conventional Mason-Allen configuration can be applied with double-loaded suture anchor safely. Recent modifications of the configurations offer no biomechanical advantage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
1
22
0
1
Order By: Relevance
“…The subscapularis tendon was repaired using a Mason–Allen suture technique with 0 Ethibond suture (Arthrex, Inc., Naples, FL). This suture technique was chosen based on previous studies regarding gapping and biomechanical strength of various rotator cuff suture repair techniques . This grasping stitch has been reported to have favorable results in minimizing gap formation and cyclic failure after rotator cuff repair .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The subscapularis tendon was repaired using a Mason–Allen suture technique with 0 Ethibond suture (Arthrex, Inc., Naples, FL). This suture technique was chosen based on previous studies regarding gapping and biomechanical strength of various rotator cuff suture repair techniques . This grasping stitch has been reported to have favorable results in minimizing gap formation and cyclic failure after rotator cuff repair .…”
Section: Methodsmentioning
confidence: 99%
“…This suture technique was chosen based on previous studies regarding gapping and biomechanical strength of various rotator cuff suture repair techniques. [24][25][26][27] This grasping stitch has been reported to have favorable results in minimizing gap formation and cyclic failure after rotator cuff repair. 25,27 The repair was performed with the forearm directly anterior in neutral rotation, the same position that the arm was in for the subscapularis tenotomy.…”
Section: Methodsmentioning
confidence: 99%
“…79 In single-row comparisons, most studies have shown that techniques that include an anterior to posterior stitch that is spanned by a medial to lateral stitch, such as the rip-stop, massive cuff stitch, lasso loop, and modified Mason-Allen outperform simple and mattress repair constructs. 48,67,85,93,95,105 In double-row techniques, the main comparisons are between traditional double-row techniques and transosseous equivalent techniques. These studies have failed to demonstrate a consistent biomechanical advantage of one technique over the other within the doublerow group regarding contact area, contact pressure, gap formation, or stiffness.…”
Section: Suture Techniquesmentioning
confidence: 99%
“…Las configuraciones más complejas, como la utilización de puntos de colchonero horizontales o los puntos de tipo Masson-Allen modificado, son más adecuados para asegurar una correcta fijación del tendón al hueso ( fig. 4) 39 . Aunque biomecánicamente más estables 40 , las configuraciones en «doble hilera» no siempre son posibles o está indicada su realización.…”
Section: Consideraciones Generalesunclassified